Managing Drinking Time, Space and Networks as Strategies for Avoiding Alcohol-Related Harm Among Young Estonian Adults - Maarja Kobin (Studies of Transition States and Societies, 2012)
Research on drinking in Estonia, mainly surveys, indicates that alcohol consumption has increased steadily over the last fifteen years. However, these quantitative studies provide little information about drinking habits and the meanings that are attributed to different consumption patterns. In addition, there is no research that explores how alcohol-related harm is controlled or managed, especially among young people. Current research on alcohol-related harm, primarily from the UK, emphasises calculated hedonism and shows clearly that drinking ‘depends on the context’. Relying on Goffman’s concept of ‘framework’, the aim of the current paper is to analyse or give structure to the ‘context’ by distinguishing the frameworks of drinking time, space and networks that guide young Estonians in their interpretations and perceptions of alcohol related harm, and that also act as a basis for legitimising drinking practices. Differentiating the frames helps to show the dynamics of drinking practices and the interactions in ‘context’. The research is based on open-ended and focus group interviews with young people from rural and urban areas in Estonia and is supported by participant observation in different situations where alcohol is consumed in order to provide a broader view and interpretation on young people’s drinking.